Antilipolytic drug boosts glucose metabolism in prostate cancer - Andersen, Kim Francis (2013)
INTRODUCTION: The antilipolytic drug Acipimox reduces free fatty acid (FFA) levels in the blood stream. We examined the effect of reduced FFAs on glucose metabolism in androgen-dependent (CWR22Rv1) and androgen-independent (PC3) prostate cancer (PCa) xenografts. METHODS: Subcutaneous tumors were produced in nude mice by injection of PC3 and CWR22Rv1 PCa cells. The mice were divided into two groups (Acipimox vs. controls). Acipimox (50 mg/kg) was administered by oral gavage 1 h before injection of tracers. 1 h after i.v. co-injection of 8.2 MBq (222±6.0 μCi) (18) F-FDG and~0.0037 MBq (0.1 μCi) (14)C-acetate, (18) F-FDG imaging was performed using a small-animal PET scanner. Counting rates in reconstructed images were converted to activity concentrations. Quantification was obtained by region-of-interest analysis using dedicated software. The mice were euthanized, and blood samples and organs were harvested. (18) F radioactivity was measured in a calibrated γ-counter using a dynamic counting window and decay correction. (14)C radioactivity was determined by liquid scintillation counting using external standard quench corrections. Counts were converted into activity, and percentage of the injected dose per gram (%ID/g) tissue was calculated. RESULTS: FDG biodistribution data in mice with PC3 xenografts demonstrated doubled average %ID/g tumor tissue after administration of Acipimox compared to controls (7.21±1.93 vs. 3.59±1.35, P=0.02). Tumor-to-organ ratios were generally higher in mice treated with Acipimox. This was supported by PET imaging data, both semi-quantitatively (mean tumor FDG uptake) and visually (tumor-to-background ratios). In mice with CWR22Rv1 xenografts there was no effect of Acipimox on FDG uptake, either in biodistribution or PET imaging. (14)C-acetate uptake was unaffected in PC3 and CWR22Rv1 xenografts. CONCLUSIONS: In mice with PC3 PCa xenografts, acute administration of Acipimox increases tumor uptake of (18) F-FDG with general improvements in tumor-to-background ratios. Data indicate that administration of Acipimox prior to (18) F-FDG PET scans has potential to improve sensitivity and specificity in patients with castration-resistant advanced PCa.